HISTORICAL ARCHITECTURAL MONUMENTS OF UZBEKISTAN: THEIR SIGNIFICANCE AND PRESERVATION (Modern education and development, 2025)
Uzbekistan, located in the heart of Central Asia, is a land rich in history, culture, and architectural wonders. As a key region on the ancient Silk Road, it has witnessed the rise and fall of empires, the flourishing of trade, and the blending of diverse cultures. Among its greatest treasures are its historical architectural monuments, which not only reflect the artistic and cultural achievements of past civilizations but also serve as a bridge between the past and the present. These monuments are of immense value, both locally and globally, and their preservation is of paramount importance.